Effectiveness of Dietary Supplement for Skin Moisturizing in Healthy Adults: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Sun, Qian; Wu, Jingping; Qian, Guofei; Cheng, Hongbin (Frontiers in Nutrition, 2022)
Background: The dietary supplement industry offers many oral cosmetics that purportedly assist in skin moisturization often with unclear evidence supporting efficacy and safety. To update the accessible proofs pertaining to the safety and effectiveness of oral dietary supplements to facilitate skin moisturizing via an all-round review and meta-analysis. Methods: Three on-line data bases (Pubmed, Embase and Cochrane Library (CENTRAL)) were retrieved from January 2000 to November 2021. An overall 66 randomized controlled trials (RCTs) of skin care were recognized. Meta-analysis was performed for dietary supplements with four or more available researches. Results: Oral collagen or ceramide resulted in a statistically significant increase of skin hydration and a decrease of TEWL (transepidermal water loss) compared to placebo. No benefits regarding the improvement of skin conditions in terms of water content and TEWL were observed for lactic acid bacteria or Lactobacillus fermented foods. A statistically significant and positive effect on skin hydration was observed for both hyaluronan and procyanidin, with unknown effects on TEWL due to insufficient RCTs. There was a non-significant improvement on the water content of stratum corneum for astaxanthin in subgroup analyses. Among the dietary supplements trialled in ≤3 RCTs, the judgment regarding their effects on skin moisturizing was prevented for inconsistent conclusions as well as the insufficient researches. All food supplements were safe throughout the researches (normally ≤24 weeks). Conclusion: Oral dietary supplements, including collagen, ceramide, hyaluronan and procyanidin, were proven to be effective for skin moisturization. At present, for skin moisturization, the proofs supporting the recommendation of other dietary supplements, such as lactic acid bacteria and astaxanthin, are insufficient.